She must be the place: sleepy sheep and the digital remediation of place in Airbnb online experiences during the first lockdown - Addis, Maria Cristina (E|C, 2021)
Short-term rental platforms have been a crucial lever in the development and support of so-called experiential tourism, based on the idea of the most intense and profound access possible to the identity and culture of the places being visited. Airbnb, in particular, proposes a travel experience that comes close to living, experiencing and practising the territory from the point of view of one of its inhabitants: around the host/guest relationship is centred an ideology of sharing and sociality that tends to neutralise the economic dimension of tourist exchange in favour of mutual knowledge and mutual enrichment. At a time when the measures of containment and distancing of bodies have obviously drastically frozen tourist flows and travel in general, the offer of virtual guided tours, video lessons and, more often, hybrid digital performances performed live, is exploding on Airbnb. We will focus in particular on a widespread and original form of rural tourism redevelopment: “guided meditation” with and by animals.